Enabling Aqueous Processing for LiNi0.5Mn1.5O4‐Based Positive Electrodes in Lithium‐Ion Batteries by Applying Lithium‐Based Processing Additives. Issue 11 (6th May 2021) - Dienwiebel, Iris; Diehl, Marcel; Heidrich, Bastian; Yang, Xiaofei; Winter, Martin; Börner, Markus
Abstract : Aqueous processing of positive electrode active materials (AMs) could enable a more economical and environmentally friendly production of lithium‐ion batteries. Intrinsically, aqueous processing of positive AMs is hampered by lithium‐proton exchange in the AM surface, leading to a poor electrochemical performance and a resulting strong increase in the pH value in the electrode paste, thereby corroding the aluminum current collector. Herein, the influence of different lithium salts as processing additive to tailor the pH value of the electrode paste, the manganese dissolution during processing, and the electrochemical performance is described for aqueous processing of LiNi0.5 Mn1.5 O4 ‐based positive electrodes. Positive electrodes, based on an aqueous LiNi0.5 Mn1.5 O4 ‐based electrode paste which is mixed with LiN(SO2 CF3 )2 (LiTFSI), achieve a comparable electrochemical performance to state‐of‐the‐art nonaqueous‐processed electrodes. Manganese dissolution into the electrode paste is examined by inductively coupled plasma‐mass spectrometry (ICP‐MS), showing that the addition of lithium salts to the electrode paste substantially decreases manganese leaching during processing. Furthermore, postmortem analysis shows that the addition of LiTFSI to the electrode paste has a positive effect not only during processing but also on charge/discharge cycling performance. Abstract : Processing additives enable aqueous processing for LiNi0.5 Mn1.5 O4 ‐based positive electrodes by hindering the lithium‐proton exchange while limiting the pH increase in the electrode paste and decreasing the manganese dissolution during processing at the same time. The addition of LiN(SO2 CF3 )2 (LiTFSI) to the electrode paste has a positive effect not only during processing but also improves the electrochemical performance of full cells.